2017
DOI: 10.1103/physreva.95.052115
|View full text |Cite
|
Sign up to set email alerts
|

Universal locality of quantum thermal susceptibility

Abstract: The ultimate precision of any measurement of the temperature of a quantum system is the inverse of the local quantum thermal susceptibility [De Pasquale et al., Nature Communications 7, 12782 (2016)] of the subsystem with whom the thermometer interacts. If this subsystem can be described with the canonical ensemble, such quantity reduces to the variance of the local Hamiltonian, that is proportional to the heat capacity of the subsystem. However, the canonical ensemble might not apply in the presence of intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…The exponentially diverging error is a consequence of the fact that for temperatures far below the lowest gap, the system is essentially in the ground state, irrespective of the exact value of T . Such an exponentially diverging error was found in various studies on low-temperature thermometry (see, e.g., [6][7][8][9][10][11][12][13][14][15][16][17][19][20][21][22]). In particular, Eq.…”
Section: Context and Main Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The exponentially diverging error is a consequence of the fact that for temperatures far below the lowest gap, the system is essentially in the ground state, irrespective of the exact value of T . Such an exponentially diverging error was found in various studies on low-temperature thermometry (see, e.g., [6][7][8][9][10][11][12][13][14][15][16][17][19][20][21][22]). In particular, Eq.…”
Section: Context and Main Resultsmentioning
confidence: 53%
“…ponentially at low temperatures [6][7][8][9][10][11][12][13][14][15][16][17]. In fact, this exponential scaling can be derived from very general arguments [18][19][20][21], based on the energy spectra of the sample and the probe, and could therefore appear to represent a fundamental limit on thermometry. However, it was recently shown that (using a measurement with infinite resolution) a sub-exponential scaling is possible in a system of strongly coupled harmonic oscillators [22].…”
mentioning
confidence: 99%
“…More generally, any measurement on the sample, implemented using a finite-sized apparatus, comes with a lower bound on the attainable resolution of, e.g., the system energy spectrum [30][31][32]. Similar restrictions apply in situations where measurements can be made on only part of a large sample [33][34][35], and clearly such finite-resolution constraints must play an important role in formulating fundamental bounds on the attainable thermometric sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although thermometrically useful non-demolition global measurements can sometimes be implemented [6,[17][18][19], these schemes rely on measurements of additive quantities and thus cannot be optimal for strongly interacting systems. This motivates the development of minimally invasive "local" thermometric strategies, aimed at inferring the global temperature from measurements on an accessible small fraction of the system [7,20].…”
Section: Introductionmentioning
confidence: 99%